2015
DOI: 10.1158/0008-5472.can-14-3307
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Immediate-Early Proteins Promote Stemness Properties in Glioblastoma

Abstract: Glioblastoma (GBM) is the most common and aggressive human brain tumor. Human cytomegalovirus (HCMV) immediate early (IE) proteins that are endogenously expressed in GBM cells are strong viral transactivators with onconcogenic properties. Here, we show how HCMV IE are preferentially expressed in glioma stem-like cells (GSC), where they co-localize with the other GBM stemness markers, CD133, Nestin, and Sox2. In patient-derived GSC that are endogenously infected with HCMV, attenuating IE expression by an RNA-i-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 48 publications
1
66
2
Order By: Relevance
“…[34]. Furthermore, HCMV IE1 can promote glioblastoma stemness, cell-cycle progression and survival demonstrating a novel role of IE1 as potent driver for glioblastoma stem-like cells [35] and revealing that HCMV infection might promote pathogenesis in gliomas [36]. In addition, there are studies demonstrating that the IE1 expression increases the proliferation rate in primary glioblastoma cells via the suppression of p53 protein and the activation of Akt signaling [37][38][39] inducing the expression of a negative p53 protein regulator [40].…”
Section: Introductionmentioning
confidence: 99%
“…[34]. Furthermore, HCMV IE1 can promote glioblastoma stemness, cell-cycle progression and survival demonstrating a novel role of IE1 as potent driver for glioblastoma stem-like cells [35] and revealing that HCMV infection might promote pathogenesis in gliomas [36]. In addition, there are studies demonstrating that the IE1 expression increases the proliferation rate in primary glioblastoma cells via the suppression of p53 protein and the activation of Akt signaling [37][38][39] inducing the expression of a negative p53 protein regulator [40].…”
Section: Introductionmentioning
confidence: 99%
“…Soroceanu et al found that attenuation of endogenous IE expression in glioma stem-like cells inhibited growth of the tumor cells in spheres which is a technique that enriches for stem-like cells. 35 Simultaneously, non CMV-expressing cell lines that were infected with CMV had an increase in self-renewal and proliferation. The same group found that CMV pp71 was preferentially expressed in CD133+ glioma stem-like cells.…”
Section: Role In Glioma Pathogenesismentioning
confidence: 99%
“…These cells have been shown to demonstrate stem cell properties 35,36,38,39 and therefore may represent the tumor population driving tumor growth, invasiveness and treatment resistance. Therefore, although CMV based immunotherapy may eliminate only a portion of GBM tumor cells, these changes remain clinically significant due to the downstream impact of removing this cell population (Figure 1a).…”
Section: Mechanisms Of Action Of Anti-cmv Based Immunotherapymentioning
confidence: 99%
“…self-renewal) and proliferation of glioma stemlike cells in vivo. [21] Follow-up studies demonstrated that IE1 promotes the tumor phenotype in these settings through inactivation of the p53 and Rb tumor suppressor proteins and through activation of the PI3-K/AKT signaling pathway. [22] Long-term HCMV infected glioma cultures demonstrated upregulation of key signaling mediators such as SOX2, STAT3, BMX and IL-6.…”
Section: Hcmv and Gbm Associationmentioning
confidence: 99%